2022
DOI: 10.3389/fpubh.2022.852612
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Identification of Unsafe Acts in Deep Coal Mine Workers Based on Grounded Theory and HFACS

Abstract: The risk factors affecting workers' unsafe acts were comprehensively identified by Human Factors Analysis and Classification System (HFACS) and grounded theory based on interview data and accident reports from deep coal mines. Firstly, we collected accident case and field interview data from deep coal mines issued by authoritative institutions. Then, the data were coded according to grounded theory to obtain relevant concepts and types. The HFACS model was used to classify the concepts and categories. Finally,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The dominant factors which cause unsafe act practices during work among others are management of company's resources, process in organization, and company's failure in solving issues in the workplace. In addition, some of the common practices of unsafe acts are inappropriate placement of employees or inappropriate workload given to employees, failure in reinforcing prevailing regulations, and work tools or equipment which do not meet required technical specifications (Yang et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The dominant factors which cause unsafe act practices during work among others are management of company's resources, process in organization, and company's failure in solving issues in the workplace. In addition, some of the common practices of unsafe acts are inappropriate placement of employees or inappropriate workload given to employees, failure in reinforcing prevailing regulations, and work tools or equipment which do not meet required technical specifications (Yang et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The grounded theory approach requires researchers to continuously collect and analyze data and to continuously supplement and improve emerging concepts and categories [ 38 ]. When the newly collected data cannot be classified in new ways, this indicates that the theory has reached saturation [ 43 ]. After the first phase was completed, we organized the second phase of data collection and analysis to confirm whether new categories or concepts would be generated and found that new concepts and categories were indeed generated in the second phase, for which we organized the third phase.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous researchers in the field of coal mine research have applied the HFACS method to examine unsafe behaviors and human factors contributing to accidents. For example, Niu and Yan (2016) employed an enhanced HFACS model to conduct a gray correlation degree analysis of coal mine accident causation, while Yang, Yang, Wang, Zhu, and Qin (2022) investigated the identification of risk factors associated with unsafe behaviors among coal mine workers using the underlying theory and the depth of HFACS. Fa et al (2021) explored the hierarchical relationship between human and organizational elements in coal mine accidents by progressively modifying the HFACS‐coal mines framework.…”
Section: Development Of An Hfacs‐based Human Factors Model For Coal M...mentioning
confidence: 99%